Central motor conduction in human chronic Chagas' disease - M.J. Segura; O.M. Genovese; Elsa Segura; Olga P. Sanz; R.E.P. Sica (Arquivos de Neuro-Psiquiatria)
The possible involvement of spinal alpha motor neurons, dorsal root ganglia and sensory fibers in human chronic Chagas' disease was previously demonstrated. More recently neuropsychological and sensory evoked potentials studies suggest the existence of central nervous system abnormalities in these patients. We assessed the state of central motor pathways in 46 patients with chronic Chagas' disease and 30 healthy volunteers by means of percutaneous cortical and spinal electrical stimulation. No significative slowness in pyramidal tracts (PT) conduction was found when comparing both groups. Neither any individual patient exhibited abnormally delayed PT conduction values beyond the upper normal limit of the healthy volunteers. These results suggest that, in contrast with other neural systems, the large myelinated PT fibers are usually spared in human chronic Chagas' disease.